Estudo prosódico sobre as manifestações de foco - Delia Ribeiro Leite (2009)
This study objectified to analyze the prosodic pattern of the manifestations of focus in Brazilian Portuguese. Specifically, we aimed identify, through analysis of acoustic parameters of fundamental frequency, intensity, duration and pauses, the pattern of the prosodic contrastive focus and see if it is modified due to its overlap with the syntactic focus. The corpus is constituted of POBH PROJECT, proposed by Magalhães (2000). We identified the occurrence of prosodic contrastive focus, and were separated where it was attributed only by prosody those in which there was overlap with the syntactic prosodicfocus. After performed the acoustic analysis of data, observing the prosodic parameters listed above, the results in sentences in which there was only prosodic focus were compared with those co-occurring prosodic and syntactic focus in order to verify if the overlap influence of the prosodic pattern. The results confirmed that the prosodic contrastive focus involves the increase in the values of f0 and also indicated that the duration is a relevant parameter for the phenomenon. The overlap with the syntactic focus, in turn, alters the pattern of prosodic contrastive focus, it causes the elevation of the values of f0. Based on the results, it wasproposed then the characterization of the phenomenon of focus.